MORAL AGENCY IN CHALLENGING CONTEXTS: AN INTERPRETATIVE PHENOMENOLOGICAL INVESTIGATION OF ELECTION COMMISSIONERS’ EXPERIENCES - Effendi, Robby; Fadilah, Risydah; Lubis, Suaidah; Juliana; Putri, Dwi; Bangun, Siti Sariah; Butar Butar, Fransisca Mularia (International Journal of Cultural and Social Science, 2026)
This research investigates the lived realities of election commissioners operating under persistent institutional constraints during a local electoral process. Contemporary electoral research frequently depicts election administrators merely as procedural agents, providing insufficient insight into their ethical and psychological dimensions. This inquiry seeks to elucidate how election commissioners perceive pressure, moral obligation, professional dedication, and self-identity within the context of their daily responsibilities. Employing an interpretative phenomenological framework, information was gathered from six local election commissioners through solicited written responses via electronic mail, facilitating profound contemplation on their professional encounters. The gathered data underwent analysis through reflective thematic evaluation. The outcomes unveil four interrelated themes: ongoing structural pressures necessitating ethical discretion, moral impetus extending beyond mere procedural adherence, organizational allegiance functioning as a psychological safeguard, and the continual evolution of professional identity through ethical introspection. These results suggest that electoral integrity arises from the dynamic interplay between individual values and institutional expectations rather than solely from formal regulations. The study enhances psychological insights into moral agency within public service and underscores the necessity for institutional backing, ethical resilience training, and psychosocial support for election officials.